Serum neurofilament light levels in natalizumab-treated patients with multiple sclerosis who switch to extended interval dosing from every-4-week dosing in real-world clinical practice. (February 2023) - Foley, John; Xiong, Kuangnan; Hoyt, Tammy; Singh, Carol M; Riddle, Evan; de Moor, Carl; Plavina, Tatiana; Campbell, Nolan
Background: Serum levels of neurofilament light chain (sNfL) are a potentially useful biomarker for assessing the efficacy of multiple sclerosis (MS) treatments. Objective: To compare levels of sNfL in patients with MS who switched from natalizumab every 4 weeks (Q4W) to extended interval dosing (EID) and patients who remained on Q4W dosing in real-world clinical practice. Methods: This was a retrospective analysis of samples from patients treated with natalizumab from 2010 to 2015 at a single center in the United States. Levels of sNfL were compared in patients who stayed on Q4W dosing or who switched to EID (parallel-arm analyses) and during Q4W and EID periods in patients who switched to EID (pre- and post-switch analyses). Results: The analysis included 139 patients (Q4W: n  = 79; EID: n  = 60). After adjustment, levels of sNfL did not significantly differ between patients who remained on Q4W dosing and those who switched to EID in parallel-arm analyses (adjusted Q4W-EID difference = 0.51 pg/mL; p  = 0.60) or pre- and post-switch analyses (adjusted difference = 0.96 pg/mL; p  = 0.10). Conclusion: These sNfL biomarker results suggest that the effectiveness of natalizumab is maintained in patients who switch from Q4W dosing to EID.